Preparation and Characterization of Porous Biphasic Calcium Phosphate for Biomedical Application - Pan, Yusong; Xu, Chuyang; Rong, Huayuan (Asian Journal of Chemistry, 2013)
The porous biphasic calcium phosphate scaffolds was prepared by wet precipitation method combing with sintering technology. The microstructure and morphology were investigated by XRD, SEM and FTIR. The results revealed that the porous biphasic calcium phosphate scaffolds exhibit abundant porous structure and this special porous structure is beneficial to the growth of chondrocytes and effectively improves the interfacial bonding strength between implant material and natural tissue. The porosity of the scaffolds increased with the rise of stearic acid content. The investigation on the compressive mechanical properties revealed that the compressive strength of the porous biphasic calcium phosphate scaffolds decreased with the rise of stearic acid content and porosity.